A systems approach to evaluating the air quality co-benefits of US carbon policies - Thompson, Tammy M.; Rausch, Sebastian; Saari, Rebecca K.; Selin, Noelle Eckley (Nature climate change, 2014)
Because human activities emit greenhouse gases (GHGs) and conventional air pollutants from common sources, policy designed to reduce GHGs can have co-benefits for air quality that may offset some or all of the near-term costs of GHG mitigation. We present a systems approach to quantify air quality co-benefits of US policies to reduce GHG (carbon) emissions. We assess health-related benefits from reduced ozone and particulate matter (PM2.5) by linking three advanced models, representing the full pathway from policy to pollutant damages. We also examine the sensitivity of co-benefits to key policy-relevant sources of uncertainty and variability. We find that monetized human health benefits associated with air quality improvements can offset 26-1,050% of the cost of US carbon policies. More flexible policies that minimize costs, such as cap-and-trade standards, have larger net co-benefits than policies that target specific sectors (electricity and transportation). Although air quality co-benefits can be comparable to policy costs for present-day air quality and near-term US carbon policies, potential co-benefits rapidly diminish as carbon policies become more stringent.
Gesehen am 18.04.2023